Re-visiting the Park: Reviving the “Cultural Park for Children” in Sayyeda Zeinab in the shadows of Social Sustainability - ZEINAB SHAFIK; MENNAT-ALLAH EL-HUSSEINY (Journal of Contemporary Urban Affairs, 2019)
This paper aims to question the level of success of one of Egypt’s contemporary architectural milestones which is the Aga-Khan Award-winning project of the Child Park in Sayyeda Zeinab - designed by the Egyptian architect Abdel-Halim Ibrahim; from a community participation perspective. Stemming from the fact that the level of successful community participation in architecture and urban design projects affects the sustainability of the added value, this paper tackles the current process of operation of the Park and the adjacent pedestrian street, as complementary aspects of a community participatory process, and evaluates the social sustainability of the project as well. The study sheds light on the operation of the park after twenty-eight years of the initiation of the project, it explores its functional and social role in the district of Sayyeda, located at the centre of Cairo city.In order to achieve this end, the paper adopts a two-fold methodology. Based on those two main research approaches, the paper concludes with a framework and several guidelines to enhance the social sustenance of the place through rephrasing the park’s role in relation to the changing needs of the community.